Pengaruh Profitabilitas, Leverage, Likuiditas, dan Dewan Komisaris Independen Terhadap Pengungkapan Islamic Social Reporting (ISR) Pada Perbankan Syariah Di Indonesia Tahun 2015-2018 - Rimi Gusliana Mais; Tuti Alawiyah (Jurnal Ekonomi, 2020)
This study aims to determine and analyze the effect of profitability, leverage, liquidity, and independent commissioners on the disclosure of Islamic Social Reporting (ISR) in Islamic Banking in Indonesia in 2015-2018. This study uses a causal research strategy (cause and effect) with a quantitative approach that is measured using a panel data regression-based method with the help of Eviews 10 software. The population of this study is all Islamic Commercial Banks registered with the Financial Services Authority (OJK) from 2015 to 2015. 2018. The sample was determined based on the purposive sampling method, with a total sample of 10 Islamic Commercial Banks so that the total observations in this study were 40 observations. The type of data used in this study is secondary data in the form of financial reports that are downloaded through the website of each Islamic commercial bank. The data analysis method used in this research is multiple regression test and hypothesis testing. Based on the results and discussion, it shows that profitability has a significant negative effect on Islamic Social Reporting (ISR), Leverage has a significant positive effect on Islamic Social Reporting (ISR), negative liquidity has no significant effect on Islamic Social Reporting (ISR) and the Independent Board of Commissioners has no significant effect. on Islamic Social Reporting (ISR) on Islamic banking in Indonesia for the 2015-2018 period.